2012
DOI: 10.1194/jlr.m029512
|View full text |Cite
|
Sign up to set email alerts
|

Production of wax esters in plant seed oils by oleosomal cotargeting of biosynthetic enzymes

Abstract: Wax esters are neutral lipids exhibiting desirable properties for lubrication. Natural sources have traditionally been whales. Additionally some plants produce wax esters in their seed oil. Currently there is no biological source available for long chain length monounsaturated wax esters that are most suited for industrial applications. This study aimed to identify enzymatic requirements enabling their production in oilseed plants. Wax esters are generated by the action of fatty acyl-CoA reductase (FAR), gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(93 citation statements)
references
References 21 publications
(40 reference statements)
5
88
0
Order By: Relevance
“…In addition to the examples that we detail, the production of many other unusual lipids, such as wax esters and epoxy-fatty acids, has been demonstrated in Arabidopsis [84,85]. However, the development of an effective transformation method has allowed transgenic Camelina lines to be developed almost as easily as with Arabidopsis.…”
Section: Resultsmentioning
confidence: 93%
“…In addition to the examples that we detail, the production of many other unusual lipids, such as wax esters and epoxy-fatty acids, has been demonstrated in Arabidopsis [84,85]. However, the development of an effective transformation method has allowed transgenic Camelina lines to be developed almost as easily as with Arabidopsis.…”
Section: Resultsmentioning
confidence: 93%
“…Primers used are listed in Supplemental Table S3. DGAT1, PDAT, and amiRNA sequences were cloned into modified pUC18ENTR2 vectors (Heilmann et al, 2012) with napin as a promotor. Final constructs were made by combining four different pUC18ENTR2 vectors (empty or containing a gene/amiRNA) using Gateway technology (Invitrogen) with a modified pCAMBIA33.1 vector (Hornung et al, 2005).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Coexpression of the jojoba FAR and WS genes with a jojoba fatty acid elongase (ScFAE) in Arabidopsis was reported to result in significant accumulation of wax esters in seed oil (Lardizabal et al, 2000), however, this promising result was not followed on by the authors. More recently, Heilmann et al co-expressed an endoplasmic reticulum (ER)-localized mouse WS with a mouse peroxisomal FAR re-targeted to the ER to generate wax esters in Arabidopsis seeds with principally C18 and C20 fatty acid and fatty alcohol components (Heilmann et al, 2012). The authors reported that linking theses enzymes at their amino-termini to oleosin, an oil body structural protein, wax ester contents as high as 45 μg/mg seed weight or ∼15% of the total seed oil were achieved.…”
Section: Fish Oil (Omega-3 Lc-pufas) Production In Camelinamentioning
confidence: 99%